Relação entre desenvolvimento e medidas morfométricas de bezerros oriundos de cruzamento alternado contínuo das raças Charolês e Nelore - Fernandes, Tiago Albandes (2019)
The aims were to measure the morphometric measurements and to evaluate the relationship between body weight gain and the increase of morphometric measurements of Nellore (N) and Charolais (C) breeds, and their second (G2) and third crossbreeds. (G3) generation. A total of 159 calves were used (C = 29; N = 22, G2 - ¾ C ¼ N = 21; ¾ N ¼ C = 9 and G3 - 5/8 C 3/8 N = 44; 5/8 N 3 / 8 C = 34). Body weight (BW), average daily gain (ADG), arm perimeter (AP), thoracic perimeter (TP), body length (BL) and croup height (CH) were taken after birth, 63, 210 and 365 days of age. Measurement increments were determined by the difference between them divided by the interval between them. Charolais animals were higher for BW, TP and BL than the Nellore, being the latter superior in RH. In the generations the predominance of Charolais genes in the genotypes provided higher measurements of BW and TP in G2, whereas the predominance of Nelore genes resulted in higher measurements of RH in both generations. Crossbred animals were superior to purebred animals in all measures, presenting significant heteroses. Differences were greater in relation to Nellore animals in BW, TP and BL measurements, and larger in relation to Charolais for RH. C animals were superior to N in BW, ADG, BL and TP gains in the BW gain by RH gain ratio, being the Nelore superior in RH gain. In G2, the predominance of C genes in genotypes provided greater gains in BW, ADG, AP and TP. Crossbred animals of both generations were superior to purebred in BW, BL, and RH gains. G3 animals were superior to pure animals in gains of ADG, AP and TP. In the relationship between gain of BW by gain of body measurements no differences were observed between pure and crossed. Charolais animals have larger muscularity measurements than Nelore animals, being the last ones higher. Crossbred animals have higher development compared to purebred animals, determining significant heterosis values. Morphometric measurements can be taken and used as good indicators of weight gain and body development.